The constitutional reform in Kazakhstan: Nur Otan’s role in legitimizing the procedure of constitutional change - Didarbekov, Ualikhan; Aitmukash, Mariyam (Nazarbayev University Graduate School of Public Policy, 2017)
After being a country with a powerful presidential system for last 26 years, Kazakhstan introduced a few but essential changes into its constitution this year. As a democratic country, Kazakhstan has undergone several significant constitutional reforms since its independence from the Soviet Union. The last one had occurred recently when the President of the country, Nursultan Nazarbayev, offered a transfer of power from President’s Administration onto Parliament and Prime Minister’s Office of Kazakhstan. The aim of these recent changes was to strengthen the Parliament’s role in dealing with legislations and make Prime Minister's Office more independent in developing a social and economic condition of the country. Indeed, president of the country wants to make ministries of the Republic of Kazakhstan to be more independent and strong in solving the inner problems of the country, while he is focusing on more global issues. Thus, the president’s decision to distribute the power was made only to improve and develop the state’s current political and economic conditions. Since good governance is the key to economic development, this decision of N.Nazarbayev was supported by many actors in the country including the "Nur Otan" Democratic People's Party (Nur Otan). In this paper, we discuss this transfer of power from the president to other branches of government such as parliament and ministries. To do so, researchers analyzed this particular constitutional reform from the viewpoint of the Nur Otan, people, and the international community...
Keywords: constitutional changes; legitimate system; democratic; separation of power; parliament; president; participatory; responsiveness; constitutional reform